Mental disorders and psychosocial support during the first year after total laryngectomy: A prospective cohort study. (December 2013) - Keszte, J.; Danker, H.; Dietz, A.; Meister, E.; Pabst, F.; Vogel, H.‐J.; Meyer, A.; Singer, S.
<x xml:space="preserve">Abstract</x> Objectives To assess the frequency of mental disorders and the use of psychosocial services in laryngectomised patients during the first year after surgery. Design Multicentre prospective study including six interviews. Data regarding psychiatric comorbidity 3 months (3 m) and 1 year (12 m) after total laryngectomy (TLE) are reported in this study. Setting Structured interviews were conducted at nine hospitals and three rehabilitation centres in Germany. Participants One hundred and seventy‐one patients were interviewed at both time‐points. Main outcome measures Structured clinical interview for DSM‐IV (SCID). Results Mental disorders were diagnosed in 25% of the patients (3 m) and in 22% of the patients (12 m), respectively. Six per cent of the patients developed a mental disorder during the first year after total laryngectomy. In general, male and female patients suffered from mental disorders with equal frequency (3 m: 23% versus 37%; P = 0.26; 12 m: 22% versus 21%; P = 1.00). Women suffered more often than men from post‐traumatic stress disorder (3 m) (P = 0.01) and generalised anxiety disorder (12 m) (P = 0.01). Of the patients who had acquired no voice, 80% suffered from alcohol dependence (P = 0.01). There were no differences between men and women in receiving any kind of counselling (P = 0.79) or psychotherapy/psychiatric treatment (P = 0.47). Of those patients diagnosed with any mental disorder 3 months after total laryngectomy, 7% had received psychotherapy 1 year after total laryngectomy. None of the patients diagnosed with alcohol dependence received psychotherapy or psychiatric treatment. Conclusions Mental disorders occur in laryngectomees as frequently in men as they do in women. Total laryngectomised patients who were mentally ill did not receive enough psychotherapeutic or psychiatric support. As mental health seems to be related to successful voice restoration, future research should develop and evaluate special psychosocial supportive programmes for patients with laryngeal cancer, especially regarding alcohol dependence treatment.